Crtitical events: An anthropological perspective on contemporary India - Das, Veena (New Delhi Oxford university press, 2018)
Critical Events recasts the anthropological understanding of individual bodies and social bodies, as well as the creation of community by looking at moments of rupture and their implications for redefining social life in contemporary India. Ranging from the Partition of India to the industrial disaster in Bhopal, the events examined in the book illuminate and transform the way anthropology generates its concepts.
Keywords: Critical Events